PLAYING HAND EYE COORDINATION ON PPLP ARREST PERFORMANCE WEST KALIMANTAN - Zakaria, Zakaria; Purnomo, Edi; Juni Samodra, Y Touvan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aimed of thay study to determine effect hand eyer coordination on archery of west kalimantan PPLP athletes. Method research used experimental desain. The subjects research are 6 peoples. Phase target test instrument. Used in this research.Hand and eyer coordination are using tennis ball. Game divided by three level with 12 theatwith the level are divided by easy, medium and difficult. Data was collected by shooting target face test. data analised by non parametric wilcoxon. The de result study showed positive effect hand and eyer coordination on archery achievement. Asymp sig (2.tailed) 0.028, probability below 0.05 (0.014 <0.05). So, Ho is rejected, which means that there are differences in the value of people who try before and after taking treatment.Â Keywords: playing, eye-hand, factory performance